HUBUNGAN PEMANFAATAN BUKU KIA DENGAN PENGETAHUAN TENTANG TANDA BAHAYA KEHAMILAN PADA IBU HAMIL - Fitria Yulastini (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2022)
The maternal mortality rate (MMR) and infant mortality rate (IMR) are still major problems in the world because they are still relatively high. Various government efforts and policies to reduce MMR and IMR are one of which is the provision of Maternal and Child Health (KIA) books. Using the KIA book is a strategy to empower the community, especially families, to maintain their health and obtain quality maternal and child health services. The aim of this research is to determine the relationship between the use of KIA books and knowledge about the danger signs of pregnancy among pregnant women at the Bangket Parak Polindes, Teruwai Community Health Center Work Area. This research is a correlational analytical research with a cross-sectional approach. The total sample was 51 pregnant women using a total sampling technique. The data collection tool used a questionnaire and was analyzed using the Chi-Square test. The research results showed that the majority of respondents did not use the KIA book, namely 29 people (56.9%), and 22 respondents (43.1%) used the KIA book. Meanwhile, based on knowledge, the majority of respondents had poor knowledge, namely 21 people (41.2%) and the fewest were respondents with good knowledge, namely 12 people (23.5%). Chi-Square test results show a p-value of 0.000 (α<0.05). It can be concluded that there is a significant relationship between the use of KIA books and pregnant women's knowledge about the danger signs of pregnancy at the Bangket Parak Polindes, Teruwai Community Health Center Work Area.